Epithelial plasticity, epithelial-mesenchymal transition, and the TGF-β family - Katsuno, Yoko; Derynck, Rik (Developmental cell, 2021)
Epithelial cells repress epithelial characteristics and elaborate mesenchymal characteristics to migrate to other locations and acquire new properties. Epithelial plasticity responses are directed through cooperation of signaling pathways, with TGF-β and TGF-β-related proteins playing prominent instructive roles. Epithelial-mesenchymal transitions (EMTs) directed by activin-like molecules, bone morphogenetic proteins, or TGF-β regulate metazoan development and wound healing and drive fibrosis and cancer progression. In carcinomas, diverse EMTs enable stem cell generation, anti-cancer drug resistance, genomic instability, and localized immunosuppression. This review discusses roles of TGF-β and TGF-β-related proteins, and underlying molecular mechanisms, in epithelial plasticity in development and wound healing, fibrosis, and cancer.